THE INFLUENCE OF PROFITABILITY AND FUNDING DECISIONS ON COMPANY VALUE - Hartika, Novitania Mutiara; Iswara, Ulfah Setia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This research aimed to examine the effect of profitability and fund decisions on the firm value of Food and Beverage companies that were listed on the Indonesia Stock Exchange during 2017-2020. The research was quantitative. Furthermore, the data collection technique used purposive sampling, in which the sample was based on the criteria given. In line with that, there were 64 samples from 16 Food and Beverage companies with 4 years of observations (2017-2020). The data analysis technique used multiple linear regression. The research result concluded that profitability which was measured by Return On Equity had a significant positive effect on the firm value. However, That measured Profitability by the Net Profit Margin had a positive effect but did not on the firm value. Fund decisions that were measured by Debt Equity Ratio had a positive effect but did not affect firm value. In conclusion, that profitability (ROE) has an influence on firm value of food and beverage companies.